Structural elucidation of how ARF small GTPases induce membrane tubulation for vesicle fission - Xiaoyun Pang; Yan Zhang; Kunyou Park; Zhenyu Liao; Jian Li; Jiashu Xu; Minh-Triet Hong; Guoliang Yin; Tongming Zhang; Yaoyu Wang; Edward H. Egelman; Jun Fan; et al. (Proceedings of the National Academy of Sciences, 2025)
ADP-Ribosylation Factor (ARF) small GTPases have been found to act in vesicle fission through a direct ability to tubulate membrane. We have pursued cryoelectron microscopy (EM) to reveal at 3.9 Å resolution how ARF6 assembles into a protein lattice on tubulated membrane. Molecular dynamics simulation studies confirm and extend the cryo-EM findings. The ARF6 lattice exhibits features that are distinct from those formed by other membrane-bending proteins. We identify protein contacts critical for lattice assembly and how membrane insertion results in constricted tubules. The lattice structure also enables docking by GTPase-activating proteins (GAP) to achieve vesiculation. We have also modeled ARF1 onto the ARF6 lattice, and then pursued vesicle reconstitution by the Coat Protein I (COPI) complex to further confirm that the ARF lattice acts in vesicle fission. By elucidating how an ARF protein tubulates membrane at the structural level, we have advanced the molecular understanding of how this class of transport factors promote the fission stage of vesicle formation.